Knowledge Management And Organizational Performance: The Neglected Role Of Institutional Accounting Practices - Ayodele, Ozavize Freida; Yao, Liu; Haron, Hasnah; Eaw, Hooi-Cheng (unimas, 2024)
Indexed by WOS/Scopus/MyCite